Journal of the American Geographical Society of New York - American Geographical Society of New York. (New York : American Geographical Society of New York, 1873)
Although its strengths lie in the articles on the Western Hemisphere, some extremely valuable materials from other explorations can be found. Some of the first letters written by David Livingston from his mission in central Africa are included, as well as articles by other eminent explorers of that time. Though the publication changed names and formats during its history, its basic organization was the same as that of the Society's earlier publication, the Bulletin of the American Geographical and Statistical Society. Records of the Society's transactions including membership and officers lists, charter and records of meetings comprised the first part of the Journal. Selected papers read before or contributed to the Society comprised the second part. Beginning in 1872, these were issued in an annual volume. In later years, only the papers of the Society were bound in the annual volume. Cf. American periodicals, 1741-1900. First begun as the Journal of the American Geographical and Statistical Society in 1859, this was for over 30 years the only American periodical devoted to scientific geography. Known variously as the Society's Bulletin or Journal, it contained records of much of the most important exploration and research done in the U.S. during that time and probably contained more geographic material than all other publications with the exception of government documents. Many important early government surveys such as the Pacific Railroad Surveys of 1872-3 and those of other Western or Arctic territories are recorded in the Bulletin. The official report of the Northwestern Boundary Survey of 1857-1861, which carried out the provisions of the treaty settling the Oregon question and separating American from British territory in the West, was lost. A report for the Bulletin, written by George Gibbs, the official geologist of the American party of the survey, serves as the only presently existing American account of the survey. Mode of access: Internet. 1852-1915 in 1 v.